The effects of bundling on livestock producers' valuations of environmentally friendly traits available through genomic selection. (14th November 2022) - Worden, David; Hailu, Getu; Jones, Kate; Lee, Yu Na
Abstract: This study estimates the willingness to pay (WTP) premiums for two novel traits available through genomic technologies in the dairy industry. Using a contingent valuation method to elicit WTP and the data from mail surveys collected from 486 Canadian dairy producers, we find a positive WTP premium for feed efficiency and a negative or zero WTP premium for reduced methane emissions. However, we observe positive valuations for reduced methane emissions if it is bundled with the feed efficiency trait. This finding suggests that the way private and public benefits of environmentally sustainable production alternatives are presented to livestock producers is critical, especially as the industry adapts to rising demand while holding an increasingly precarious position in environmental sustainability. Résumé: Cette étude estime le consentement‐à‐payer (CAP) des primes pour deux nouveaux caractères disponibles via les technologies génomiques dans l'industrie laitière. En utilisant une méthode d'évaluation contingente pour obtenir le CAP et les données des enquêtes postales recueillies auprès de 486 producteurs laitiers canadiens, nous trouvons un CAP une prime positive pour l'efficacité alimentaire et un CAP une prime négative ou nulle pour la réduction des émissions de méthane. Cependant, nous observons des valeurs positives pour la réduction des émissions de méthane si elle est associée au caractère d'efficacité alimentaire. Cette constatation suggère que la façon dont les avantages privés et publics des alternatives de production écologiquement durables sont présentés aux éleveurs est essentielle, d'autant plus que l'industrie s'adapte à la demande croissante tout en occupant une position de plus en plus précaire en matière de durabilité environnementale.